Doppler velocimetry in pregnant women aged 22-26 weeks at 3300 m. Preliminary study. - Vargas, Luis (2015)
To determine the normal values of pulsatility index and resistance in uterine and umbilical artery in our population to 3,300 meters. MATERIAL AND METHODS: From May 1999 to January 2000 study Doppler velocimetry was performed in 16 pregnant women between 22 and 26 weeks, randomly selected during prenatal care in the National Est Hospital, EsSalud, the city of Cusco, 3,300 meters, measuring pulsatility index and resistance in the uterine and umbilical arteries. RESULTS: upper and lower values were determined with 95% confidence for pulsatility index in umbilical artery of 1.4192 and 1.2010, respectively, and resistance index of 0.7996 and 0.7133. The upper and lower values found for pulsatility index in uterine artery are 1.0257 and 0.6625, while resistance to index were 0.6082 and 0.4758. CONCLUSIONS: This study found values of resistance index and pulsatility similar to those found at sea level uterine artery. However, the values of these indices for umbilical artery are higher than those of sea level.